2016
DOI: 10.1002/tcr.201600119
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Barium in Transition Metal Oxide Frameworks: Impact upon Superconductivity, Magnetism, Multiferroism and Oxygen Diffusion and Storage

Abstract: The role of barium in the structural chemistry of some transition metal oxides of the series "Cu, Mn, Fe,Co" is reviewed, based on its size effect and its particular chemical bonding. Its impact upon various properties, superconductivity, magnetism, multiferroism, oxygen storage is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 188 publications
0
9
0
Order By: Relevance
“…In other words, the CO 2 resistance is another important factor to consider when developing OSMs. Various perovskite-related materials (BaY­Mn 2 ­O 5+δ or LnBa­Co 2 ­O 5+δ with Ln = lanthanide elements) and oxysulfides (Pr 2 O 2 SO 4 ) have been reported to perform well as OSMs. Still, little consideration has been paid toward their CO 2 resistance, even though alkaline earth or lanthanide elements contained in these OSMs are well-known to easily form carbonate species in a CO 2 atmosphere because of their high basicity. , To the best of our knowledge, the CO 2 resistance of OSMs that are meant to be alternatives to the CeO 2 -ZrO 2 solid-solution in automobiles has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the CO 2 resistance is another important factor to consider when developing OSMs. Various perovskite-related materials (BaY­Mn 2 ­O 5+δ or LnBa­Co 2 ­O 5+δ with Ln = lanthanide elements) and oxysulfides (Pr 2 O 2 SO 4 ) have been reported to perform well as OSMs. Still, little consideration has been paid toward their CO 2 resistance, even though alkaline earth or lanthanide elements contained in these OSMs are well-known to easily form carbonate species in a CO 2 atmosphere because of their high basicity. , To the best of our knowledge, the CO 2 resistance of OSMs that are meant to be alternatives to the CeO 2 -ZrO 2 solid-solution in automobiles has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…quenching at 1200°C for the commensurate phase [41] but was not indicated for the incommensurate oxide [42]. Bearing in mind that in cobalt-based oxides the presence of alkaline earth cations favors the partial oxidation of Co 2+ into Co 3+ [48], as recently invoked for the spin chain oxide Sr3CaMn2CoO9+δ [45], this suggests that oxygen over stoichiometry should be the mechanism at play behind this different structural behavior. To unravel this intriguing problem of the actual localization of extra oxygen in these compounds, we have investigated a series of samples with the composition Sr1+x(Mn1-xCox)O3+δ, with x ranging from 0.2857 to 0.40 , all prepared in the same conditions at 1400°C in air and quenched at this temperature for the sake of comparison.…”
Section: Synthesis and Characterization Of A Large Family Of Aperiodic Structures Sr 1+x (Mn 1-x Co X )O 3+δ : How To Interpret The Oxygementioning
confidence: 85%
“…Such an oxide containing exclusively strontium was never synthesized in air due to the partial oxidation of Co 2+ into Co 3+ , imposing δ > 0. In fact, previous studies have shown that this over oxidation originates from the presence, in transition metal oxide frameworks, of alkaline earth cations which may enhance significantly the oxidation of the transition element toward a higher state during the synthesis in air. , This is exemplified by the high Tc cuprates involving the mixed valence Cu 2+ /Cu 3+ and numerous cobaltates characterized by the mixed valence Co 2+ /Co 3+ . Importantly, we have noticed that the “oxidation power” of the alkaline earth metal decreases from Ba to Sr to Ca.…”
Section: Introductionmentioning
confidence: 99%